ETIKA PENGGUNAAN CHATGPT DALAM PENDIDIKAN DAN EKONOMI ISLAM: TINJAUAN MAQASID AL-SHARI’AH - Fitria Nilamsari; Wahyu Ichsan; Rinny Asasunnaja; Fathia Sabrina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Abstract This study examines the ethical implications of ChatGPT usage in Islamic higher education, especially within the domains of Islamic economics and Sharia-based finance. As generative AI tools gain popularity among students and educators, they present both educational support potential and ethical challenges - including risks of plagiarism, diminished critical thinking, religious misinformation, and excessive technological dependence. Adopting a qualitative exploratory approach, this research integrates library studies with expert interviews involving scholars in Islamic economic thought and Islamic banking. To enrich the analysis, a machine learning-based text similarity comparison was conducted between ChatGPT’s responses and expert opinions on selected topics. This comparative analysis quantitatively measured content alignment, revealing high levels of similarity (85–90%) in Sharia banking discourse and over 90% in Islamic economic fundamentals. The study employs both thematic analysis and normative evaluation grounded in Maqasid al-Shari’ah, focusing on the preservation of religion (ḥifẓ al-dīn), upholding intellectual integrity (ḥifẓ al-ʿaql), and protection of the soul/life (ḥifẓ al-nafs). The results demonstrate that ChatGPT can be a valuable academic support tool, yet it must be used with critical supervision and scholarly validation. The paper concludes by emphasizing the urgent need for Islamic higher education institutions to develop AI ethics guidelines that are contextually rooted in Sharia principles, ensuring that AI integration enhances rather than compromises Islamic educational integrity.